How economic crises affect inflation beliefs: Evidence from the COVID-19 pandemic - Olivier Armantier; Gizem Koðsar; Rachel Pomerantz; Daphné Skandalis; Kyle Smith; Giorgio Topa; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2020)
This paper studies how inflation beliefs reported in the New York Fed's Survey of Consumer Expectations have evolved since the start of the COVID-19 pandemic. We find that household inflation expectations responded slowly and mostly at the short-term horizon. In contrast, the data reveal immediate and unprecedented increases in individual inflation uncertainty and in inflation disagreement across respondents. We find evidence of a strong polarization in inflation beliefs and we show differences across demographic groups. Finally, we document a strong link, consistent with precautionary saving, between inflation uncertainty and how respondents used the stimulus checks they received as part of the 2020 CARES Act.
Keywords: E31; E21; 330; inflation expectations; inflation uncertainty and disagreement; COVID-19 pandemic